Talking Stick Model to Increase Student Learning Activity - Ali, Damsir; Matters, Lungisile Ntsebeza; Naidoo, Zimitri Erasmus (Institute Of Advanced Knowledge and Science, 2024)
Stick learning models speak using stick media. After students can learn the main topic, students who carry sticks are responsible for answering the teacher's questions. This learning method is designed to find out how far students understand the material being taught. When a teacher does not involve students in the learning process actively, students do not get the opportunity to ask questions or give opinions. In addition, the use of minimal media in learning causes the learning process to be less effective. The method implemented by the teacher is less creative, which causes students to feel bored, and the teacher is unable to present the lesson in an interesting way. This study uses a qualitative approach with library analysis. The Talking Stick model helps the learning of students and makes them more active, responsible, confident, and independent. It also makes learning more interactive and easier to use by the teacher. Teachers and students who use this learning model can get a lot of developments and advantages in learning, but some students can still listen, but they are less able to show their speaking skills when their turn arrives.